Brief Report: Anti–Carbamylated Protein Antibodies Are Present in Arthralgia Patients and Predict the Development of Rheumatoid Arthritis. Issue 4 (28th March 2013) - Shi, Jing; van de Stadt, Lotte A.; Levarht, E. W. Nivine; Huizinga, Tom W. J.; Toes, René E. M.; Trouw, Leendert A.; van Schaardenburg, Dirkjan
Abstract: Objective: Recently, we discovered a new autoantibody system in rheumatoid arthritis (RA): anti–carbamylated protein (anti‐CarP) antibodies. These antibodies have value in predicting joint destruction; however, it is not clear whether they are present before the diagnosis of RA and whether they have value as predictors of RA development. Therefore, we studied whether anti‐CarP antibodies are present in patients with arthralgia and whether their presence is associated with the development of RA. Methods: Sera from 340 arthralgia patients who did not have clinical signs of arthritis but who were positive for IgM rheumatoid factor (IgM‐RF) and/or anti–cyclic citrullinated peptide 2 (anti–CCP‐2) and 32 healthy controls were tested for anti‐CarP IgG antibodies. Of the patients with arthralgia, 111 were IgM‐RF positive/anti–CCP‐2 antibody negative and 229 were anti–CCP‐2 antibody positive. Patients were observed for the development of RA (based on the 2010 American College of Rheumatology/European League Against Rheumatism classification criteria) during a median followup period of 36 months. Cox proportional hazards regression analysis was performed to compare the risk of developing RA between arthralgia patients who were positive for anti‐CarP antibodies and those who were negative for anti‐CarP antibodies during followup. Results: Anti‐CarP antibodies were present in the sera of 39% of the patients. One hundred twenty patients developed RA, after a median of 12 months (interquartile range [IQR] 6–24). The presence of anti‐CarP antibodies was associated with the development of RA in the entire arthralgia cohort after correction for RF and anti–CCP‐2 antibody status (hazard ratio 1.56 [95% confidence interval 1.06–2.29], P = 0.023), as well as in the anti–CCP‐2 antibody–positive subgroup (odds ratio 2.231 [95% confidence interval 1.31–3.79], P = 0.003). Conclusion: Anti‐CarP antibodies are present in patients with arthralgia, and their presence predicts the development of RA independent of anti–CCP‐2 antibodies.